Comparison of Hotel Room Costs and Activity Based Costing System Using Hotel Sarlime Calculation - Wahyuni Wahyuni (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to compare the cost of hotel rooms and the Activity Based Costing system using the Hotel Sarlim calculation. The type of data in this study is descriptive and quantitative. Data collection methods used to obtain data in this study are interviews and documentation. The analytical method used in this study is a descriptive analysis method that shows and compares the method of calculating the Cost of Hotel rooms which has been applied so far by using the Activity Based Costing System. There is a difference between the cost of the room determined by the Sarlim hotel management and the implementation of the Activity Based Costing System. The calculation of hotel room prices using the ABC method is carried out in 2 stages. The first stage of costs is traced to activities that incur costs and the second stage is to charge activity costs to products; the calculation of hotel room rental prices can be applied because the analysis uses the ABC System method according to the activities consumed in each room type.